(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2026)
The aim of this study is to determine the social appearance anxiety levels of university students and to examine how these levels differ with respect to demographic variables such as gender, age, faculty, grade level, and active sports participation. A descriptive survey model was employed in the research. The sample consisted of 621 students enrolled at Erciyes University, selected through random sampling. Data were collected using a "Personal Information Form" and the "Social Appearance Anxiety Scale," developed by Hart et al. (2008) and adapted into Turkish by Doğan in 2010. The collected data were analyzed using SPSS 25.0. Independent samples t-tests were applied for comparisons between two groups, while one-way analysis of variance (LSD post-hoc test) was used for comparisons involving three or more groups. The most notable finding of the study is that individuals who engage in sports reported significantly lower levels of social appearance anxiety compared to those who do not. These findings suggest that social appearance anxiety is a multi-layered construct shaped by the interplay of biological, sociocultural, and behavioral factors, and indicate that sports should be regarded not only as a physical activity but also as a psychological protective factor.